Studi Analisis Literasi Lingkungan pada Siswa SMP Menggunakan Angket Digital - Ningrum, Adiya Putri Satya; Wahyuni, Sri; Astuti, Sri Rejeki Dwi; Barid, Siti Shofa Assyifa’ul Qulbi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Environmental literacy plays an important role in increasing students' awareness, knowledge, and behavior towards environmental conservation, while also influencing the learning outcomes of Natural Sciences (IPA). This study aims to determine the level of environmental literacy of eighth-grade students at SMPN 2 Cluring, Banyuwangi, based on indicators of ecological knowledge, environmental awareness, cognitive skills, and environmental behavior. This study uses a descriptive method with a quantitative approach. The research sample consisted of 60 eighth-grade students selected through a convenience sampling technique. The research instrument was a Google Form-based digital questionnaire consisting of 20 questions covering four indicators of environmental literacy. The results of data analysis show that students' environmental literacy level is in the good category with an average percentage between 61% and 80%. The environmental awareness indicator reached the highest value of 81% with a very good category, while the cognitive skills indicator had the lowest value of 69% with a good category. These findings indicate that students have a fairly good understanding and sense of concern for the environment. However, improvements in critical thinking skills and cognitive skills are needed through direct experience-based learning so that environmental literacy can develop optimally.